Comparison of the Effectiveness of Mindfulness Training and Internet-Based Acceptance and Commitment Training on Academic Engagement, Mental Time Travel, and Students' Anxiety during the COVID-19 Pandemic - Fahimeh Ghasemi; Seyedeh Olia Emadian; Ramazan Hasanzadeh (Shiraz University of Medical Sciences, 2023)
Background: Today, the country's education system, especially in high school, is facing the challenge of academic failure and lack of academic motivation among students. This study aimed to compare the effectiveness of mindfulness training and internetbased acceptance and commitment training on academic engagement, mental time travel, and students' anxiety during the COVID-19 pandemic.Methods: This study was semi-experimental designed by pre-test and post-test with a control group and a follow-up period. The statistical population consisted of all the female senior high school ((including 3 years from the ninth to the twelfth grade). in districts 1 and 2 of Sari city, Mazandaran province, Iran in the academic year 2021-2022. The research sample consisted of 45 female students (15 female students from the first experimental group, 15 female students from the second experimental group, and 15 female students from the control group) from among all the female senior high school in districts 1 and 2 of Sari city in the academic year 2020-2021, and they were selected by a random multi-stage sampling method. To collect data, Schaufeli et al.'s (2002) academic engagement questionnaires, Eren's mental time travel scale (2009), and Beck anxiety inventory (1999) were used. For the experimental groups, mindfulness training and internet-based acceptance and commitment training were implemented during eight sessions, and during this period, the subjects of the control group did not receive any intervention. The data of the research were analyzed using the analysis of variance test with repeated measurements in SPSS version 26 and a significance level of 0.05.Results: Based on the demographic findings, the mean±SD age in the acceptance and commitment group was 15.98±3.17, in the ACT group it was 16.11±3.24, and in the control group it was 16.36±3.49. The results of analysis of variance with repeated measurement showed that mindfulness training and internet-based acceptance and commitment training have a significant effect on students' academic engagement, mental time travel, and anxiety (P<0.001). Also, the effectiveness of education based on acceptance and commitment on academic engagement was higher than mindfulness education (P<0.001). However, the effectiveness of mindfulness training on mental time travel and anxiety was higher than training based on acceptance and commitment (P<0.001).Conclusion: Based on the results of the analysis, it can be concluded that internet-based mindfulness training and acceptance and commitment therapy can be considered in academic engagement, mental time travel, and anxiety of students.